FAKTOR-FAKTOR YANG MEMPENGARUHI IBU BEKERJA DALAM PEMBERIAN ASI EKSLUSIF PADA BAYI USIA 0-6 BULAN DI WILAYAH KERJA PUSKESMAS BERSERI PANGKALAN KERINCI TAHUN 2018 - Romlah, Siti (Menara Ilmu, 2018)
Breast Milk (ASI) plays an important role to maintain the health and survival of the baby because breast milk is a fatty emulsion in protein, lactose and organic salts secreted by both mother's breast glands that are useful as the main food of bayidan containing antibodies both for infants and low coverage of exclusive breastfeeding achievement and the magnitude of the risk of failure in working mothers. Low awareness and awareness about the importance of exclusive breastfeeding for infants and government policy making regarding the right to leave and procurement of supporting infrastructure for the success of exclusive breastfeeding. To know the factors that prevent the working mother in giving Exclusive Breast Milk at baby 0-6 months in working area of PuskesmasKerinci Health Center. The type of research used is quantitative. This type of research is descriptive is the study provides a description or descriptive of a situation objectively. This research was conducted in the working area of PuskesKerinciPuskesmasBerseri with a population of 148 people and using obserfasi technique using univariate data analysis. Based on the data found the inhibiting factor of working mother in exclusive breast feeding in the working area of PuskesmasBerseriPangkalankerinci. The fator which inhibits the mother to work in exclusive breastfeeding is facility, leave, family support, house distance to work place in work area of PuskesmasBerseriPangkalankerinci.Keywords: Working mother, ASI Exclusion, family support